Investigation of knowledge, attitudes and perceptions of nursing staff in oncology hospital regarding the prevention and treatment of pressure ulcers - Aikaterini Vangelatou; Georgios Vasilopoulos; Ioannis Kalemikerakis; Georgia Fasoi; Evgenia Vlachou; Martha Kelesi (Ene, 2017)
Introduction: Approximately 300 million people, 3% of the world population, need palliative care or terminal care each year, including prevention and care of pressure ulcers. Aim: The aim of this study was to evaluate the knowledge, practices and attitudes of nurses of an oncology hospital in Greece on the prevention and treatment of pressure ulcers. Methodology: This is a cross-sectional study in an Oncology Hospital of Athens. The study population was nurses and their assistants working in the particular hospital. Data collection was conducted by using a specially designed research tool. In total, 150 questionnaires were distributed and 115 were collected (response rate 76.7%). The study lasted 6 months (from July 2016 to December 2016). The statistical analysis was performed with the statistical program SPSS for Windows (version 21) statistical software. Results: The study sample consisted of 115 nurses and their assistants, age 41.6 (±6.8) years old. The average length of employment of the participants was 17.1(±7.5) years. Of the total sample, 16 (13.9%) participants reported that the hospital they work organize training seminars/courses for the prevention and treatment of pressure ulcers. Almost all participants (99.1%) answered correctly to the definition of pressure ulcers. Only 42.6% of the respondents answered correctly for the best position to prevent pressure sores, while most answered correctly to the questions concerning the risk factors for the development of pressure ulcers. About half of participants (48) reported that the clinic they work use an assessment scale for pressure ulcers and 35 (72.9%) participants completed it once a day. On the total of 27 questions, the correct answers given by respondents were 20.9 (±2.8) or 77.7% with a minimum of 8 (29.6%) and maximum 27 (100%) correct answers. Conclusions: Although oncology patients often experience problems with depression, however, the hospital did not seem to systematically implement relevant education programs to inform nursing staff. The design and implementation of such programs will help provide optimal nursing care.